2010
DOI: 10.1098/rstb.2009.0216
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ecology, psychology and neurobiology within a food-hoarding paradigm

Abstract: Many animals regularly hoard food for future use, which appears to be an important adaptation to a seasonally and/or unpredictably changing environment. This food-hoarding paradigm is an excellent example of a natural system that has broadly influenced both theoretical and empirical work in the field of biology. The food-hoarding paradigm has played a major role in the conceptual framework of numerous fields from ecology (e.g. plant -animal interactions) and evolution (e.g. the coevolution of caching, spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 75 publications
0
56
0
Order By: Relevance
“…By linking behaviour, physiology, morphology and neurobiology to ecology and evolution (the 'neuroecological' approach), recent work in the field has placed memory and memory use into an ecological and evolutionary framework (Pravosudov & Smulders 2010). The leading hypothesis for the evolution of memory used to retrieve caches is the adaptive specialization hypothesis (ASH), which states that selection can modify behaviour and its underlying neural mechanisms if such modifications enhance fitness (Krebs et al 1989;Sherry et al , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…By linking behaviour, physiology, morphology and neurobiology to ecology and evolution (the 'neuroecological' approach), recent work in the field has placed memory and memory use into an ecological and evolutionary framework (Pravosudov & Smulders 2010). The leading hypothesis for the evolution of memory used to retrieve caches is the adaptive specialization hypothesis (ASH), which states that selection can modify behaviour and its underlying neural mechanisms if such modifications enhance fitness (Krebs et al 1989;Sherry et al , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…nonmanipulated by birds) food is limited and unpredictable [e.g. Pravosudov and Smulders, 2010]; (2) they rely, at least in part, on spatial memory to recover food caches, and it has been shown that food-caching species have a larger hippocampus (a brain region involved in spatial memory) compared to noncaching species [Krebs et al, 1989;Sherry et al, 1989;Pravosudov and Roth, 2013], and (3) they occur over a variety of environments, presenting a large variation in demands for food caches and hence for spatial memory [Pravosudov and Clayton, 2002;Roth et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…2007, McNamara & Houston 2009, Dingemanse & al. 2010, Pravosudov & Smulders 2010. Models of these phenomena are unavoidably becoming more complex, often requiring the use of ABMs.…”
Section: Odd May Promote More Holistic Approaches To Modeling and Theorymentioning
confidence: 99%